ChatGPT and the Creativity of Art Education Students: A Qualitative Study of Its Use in Learning - Nurmila Sari Djau; M Zainul Hafizi (Chatra: Jurnal Pendidikan dan Pengajaran, 2026)
The development of artificial intelligence technology has created new opportunities to support learning processes and foster students’ creativity in higher education. One of the most widely used technologies is ChatGPT, which assists users in accessing information, generating ideas, and completing various academic tasks. This study aims to explore the use of ChatGPT in learning and examine its contribution to the creativity of Art Education students at the Faculty of Teacher Training and Education, Tanjungpura University. The study employed a qualitative approach with an intrinsic case study design. The participants consisted of ten second-semester students selected through purposive sampling. Data were collected through semi-structured interviews and analyzed using the interactive model of Miles and Huberman. The findings reveal that ChatGPT is utilized as a source of inspiration for creativity development, a tool for content creation and learning support, a means of enhancing learning efficiency, and a resource for independent learning. However, its use also presents challenges related to technological dependency, information validity, originality of work, and academic ethics. The study concludes that ChatGPT has the potential to support students’ creativity when used critically, reflectively, and responsibly within the learning process. Perkembangan teknologi kecerdasan buatan telah menghadirkan berbagai peluang baru dalam mendukung proses pembelajaran dan pengembangan kreativitas mahasiswa di pendidikan tinggi. Salah satu teknologi yang banyak dimanfaatkan adalah ChatGPT, yang mampu membantu pengguna dalam memperoleh informasi, mengembangkan ide, dan menyelesaikan berbagai aktivitas akademik. Penelitian ini bertujuan untuk mengeksplorasi pemanfaatan ChatGPT dalam pembelajaran serta memahami kontribusinya terhadap kreativitas mahasiswa Pendidikan Seni Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura. Penelitian menggunakan pendekatan kualitatif dengan desain studi kasus intrinsik. Informan penelitian terdiri atas sepuluh mahasiswa semester dua yang dipilih melalui teknik purposive sampling. Data dikumpulkan melalui wawancara semi-terstruktur dan dianalisis menggunakan model interaktif Miles dan Huberman. Hasil penelitian menunjukkan bahwa ChatGPT dimanfaatkan sebagai sumber inspirasi dalam pengembangan kreativitas, pendukung produksi konten dan pembelajaran, sarana yang meningkatkan efisiensi belajar, serta alat bantu yang mendukung pembelajaran mandiri. Namun demikian, pemanfaatannya juga menghadirkan tantangan yang berkaitan dengan ketergantungan teknologi, validitas informasi, orisinalitas karya, dan etika akademik. Penelitian ini menyimpulkan bahwa ChatGPT berpotensi mendukung kreativitas mahasiswa apabila digunakan secara kritis, reflektif, dan bertanggung jawab dalam proses pembelajaran.